Is there a Developed Oldowan A at Olduvai Gorge? A diachronic analysis of the Oldowan in Bed I and Lower-Middle Bed II at Olduvai Gorge, Tanzania. Issue 120 (July 2018) - Proffitt, Tomos
Abstract: Debates regarding the validity of the Developed Oldowan as separate cultural facies within the Oldowan techno-complex have primarily concentrated on the Developed Oldowan B/Acheulean transition, with little attention paid to the validity of the Developed Oldowan A (DOA) as a valid technological differentiation. This study presents a diachronic technological analysis and comparison of Oldowan and DOA lithic assemblages from Olduvai Gorge, Tanzania, dated between 1.84 and 1.6 Ma, to test the validity of Leakey's original distinction between these two cultural facies. The results from this comparative analysis show very few technological differences between the lithic assemblages previously assigned to the DOA and Classic Oldowan. Significant diachronic variation in raw material availability and use is, however, identified between Bed I and Lower/Middle Bed II of Olduvai Gorge, which may go some way to explaining the originally perceived techno-cultural differences. The results suggest an increase in hominin knapping and percussive activities, as well as a clear ability to preferentially select high quality raw materials stratigraphically above Tuff IF. Technological innovation and complexity, however, does not seem to vary significantly between the Classic Oldowan and DOA assemblages. The results of this analysis along with similar studies from the wider eastern African region lead to the conclusion that the term Developed Oldowan A should no longer be used.